In‐Situ/Operando X‐ray Characterization of Metal Hydrides. Issue 10 (21st March 2019) - Liu, Yi‐Sheng; Jeong, Sohee; White, James L.; Feng, Xuefei; Seon Cho, Eun; Stavila, Vitalie; Allendorf, Mark D.; Urban, Jeffrey J.; Guo, Jinghua
Abstract: In this article, the capabilities of soft and hard X‐ray techniques, including X‐ray absorption (XAS), soft X‐ray emission spectroscopy (XES), resonant inelastic soft X‐ray scattering (RIXS), X‐ray photoelectron spectroscopy (XPS), and X‐ray diffraction (XRD), and their application to solid‐state hydrogen storage materials are presented. These characterization tools are indispensable for interrogating hydrogen storage materials at the relevant length scales of fundamental interest, which range from the micron scale to nanometer dimensions. Since nanostructuring is now well established as an avenue to improve the thermodynamics and kinetics of hydrogen release and uptake, due to properties such as reduced mean free paths of transport and increased surface‐to‐volume ratio, it becomes of critical importance to explicitly identify structure‐property relationships on the nanometer scale. X‐ray diffraction and spectroscopy are effective tools for probing size‐, shape‐, and structure‐dependent material properties at the nanoscale. This article also discusses the recent development of in‐situ soft X‐ray spectroscopy cells, which enable investigation of critical solid/liquid or solid/gas interfaces under more practical conditions. These unique tools are providing a window into the thermodynamics and kinetics of hydrogenation and dehydrogenation reactions and informing a quantitative understanding of the fundamental energetics of hydrogen storage processes at the microscopic level. In particular, in‐situ soft X‐ray spectroscopies can be utilized to probe the formation of intermediate species, byproducts, as well as the changes in morphology and effect of additives, which all can greatly affect the hydrogen storage capacity, kinetics, thermodynamics, and reversibility. A few examples using soft X‐ray spectroscopies to study these materials are discussed to demonstrate how these powerful characterization tools could be helpful to further understand the hydrogen storage systems. Abstract : Multimodal synchrotron radiation X‐ray tools, including soft and hard X‐rays interacting with electrons and atoms within metal hydrides, are discussed. The emitted photons and electrons are monitored to understand hydrogen release and uptake in metal hydrides.